2014
DOI: 10.1155/2014/279075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Noradrenaline on the Virulence Properties ofCampylobacterSpecies

Abstract: Campylobacter species cause a spectrum of illnesses in humans. The type of illness and the outcome is dependent on the virulence of the infecting pathogen strain and host immune status. Acute stress can seriously compromise host immunity and increase susceptibility to infection. Noradrenaline (NA) is a stress hormone. Several studies have shown that it stimulated growth and increased the pathogenicity of organisms including E. coli and Campylobacter jejuni. However, the effect of NA on other Campylobacter spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 44 publications
6
17
0
1
Order By: Relevance
“…The presence of catecholamines resulted in a significant increase in growth for most isolates, and in the increased adhesion of Caco-2 cells for MF716, and in the increased invasion of Caco-2 cells for MF12581, SS72 and SS165, respectively. Similar results have been previously reported [15][16][17]. Increased growth was observed in response to epinephrine and norepinephrine, which has been widely reported [15][16][17].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The presence of catecholamines resulted in a significant increase in growth for most isolates, and in the increased adhesion of Caco-2 cells for MF716, and in the increased invasion of Caco-2 cells for MF12581, SS72 and SS165, respectively. Similar results have been previously reported [15][16][17]. Increased growth was observed in response to epinephrine and norepinephrine, which has been widely reported [15][16][17].…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have been previously reported [15][16][17]. Increased growth was observed in response to epinephrine and norepinephrine, which has been widely reported [15][16][17]. In contrast to Xu et al (2015), who observed increased growth in NCTC 11168 with the addition of epinephrine, the opposite effect was observed in our study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations